1997
DOI: 10.1074/jbc.272.47.29829
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Receptor Substrate-2 (IRS-2) Can Mediate the Action of Insulin to Stimulate Translocation of GLUT4 to the Cell Surface in Rat Adipose Cells

Abstract: Insulin receptor substrates-1 and -2 (IRS-1 and -2) are important substrates of the insulin receptor tyrosine kinase. Previous studies have focused upon the role of IRS-1 in mediating the actions of insulin. In the present study, we demonstrate that IRS-2 can mediate translocation of the insulin responsive glucose transporter GLUT4 in a physiologically relevant target cell for insulin action. Co-immunoprecipitation experiments performed on cell lysates derived from freshly isolated rat adipose cells incubated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
1
1

Year Published

1999
1999
2001
2001

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 38 publications
3
27
1
1
Order By: Relevance
“…To our knowledge, this is the first study to show the physiological relevance of an IRS-2-mediated pathway in insulin-induced glucose uptake. In agreement with our findings Zhou et al (34) showed that overexpression of IRS-2 in rat adipocytes was able to increase insulin-stimulated Glut4 translocation. In contrast to our work Higaki et al (35) could not detect a difference in insulin-induced glucose uptake in isolated muscle of IRS-2 KO mice compared with wild type animals.…”
Section: Discussionsupporting
confidence: 83%
“…To our knowledge, this is the first study to show the physiological relevance of an IRS-2-mediated pathway in insulin-induced glucose uptake. In agreement with our findings Zhou et al (34) showed that overexpression of IRS-2 in rat adipocytes was able to increase insulin-stimulated Glut4 translocation. In contrast to our work Higaki et al (35) could not detect a difference in insulin-induced glucose uptake in isolated muscle of IRS-2 KO mice compared with wild type animals.…”
Section: Discussionsupporting
confidence: 83%
“…Previous work in 3T3-L1 adipocytes showed that interference with the IRS-1-IR interaction did not cause inhibition of insulin-stimulated glucose transport, suggesting that alternate pathways exist in these cells (46). More recently, Zhou et al (50) have shown that, in rat adipocytes, overexpression of high levels of IRS-1 as well as of IRS-2 increased basal and insulin-stimulated Glut4 levels in the plasma membranes indicating that both IRSs may signal Glut4 translocation when overexpressed in cells. Supramaximal IRS-2 phosphorylation or IRS-2 overexpression caused by IRS-1 deficiency may also be responsible for the residual insulin-stimulated glucose transport in soleus muscles of IRS-1 knock out mice (20).…”
Section: Discussionmentioning
confidence: 99%
“…At these low levels, overexpression of wild-type receptors in L6 as in other cells (22) is accompanied by little change in maximal insulin effects on most signaling events and cell responses. However, a 3-10-fold decrease in the ED 50 for insulin effect on IRS-1 and IRS-2 phosphorylation and on glycogen synthase activity and thymidine incorporation could be consistently detected (Table I). These cells express fully functional GLUT4 transporters (21,(23)(24)(25)(26)(27).…”
Section: Methodsmentioning
confidence: 99%
“…IRS-2 was identified as a 190-kDa protein that is rapidly tyrosinephosphorylated in response to insulin and that partially compensates for the lack of IRS-1 in various insulin actions (20,22). For example, IRS-2, like IRS-1, is capable of participating in insulin signal transduction pathways, leading to the recruitment of GLUT4 (23). IRS-3 was first described in rat adipocytes as a 60-kDa protein that is rapidly tyrosine-phosphorylated in response to insulin, and it is considered to be a direct substrate of the activated insulin receptor (5,6,21,24 -26).…”
mentioning
confidence: 99%